Recreation, Settlement, and the Welcoming Community: Mapping Community with African-Canadian Youth Newcomers. (26th May 2016) - Campbell, Graham; Glover, Troy D.; Laryea, Edwin
ABSTRACT: The literature on newcomer settlement concentrates almost exclusively on young children and adults, leaving a sizable gap in research related to adolescents. Accordingly, this research project explored the role of community places in the settlement experiences of adolescent immigrants to Canada from Africa. Data were gathered through a cognitive mapping exercise with youth participants who engaged in a larger research project exploring engagement of traditionally underrepresented groups in community-based planning practices. Through thematic analysis of transcripts, videos, and maps, major themes of home and family, social places, and support networks were identified as important in the context of settlement and the perception of a welcoming community. Issues of safety and exclusion were also raised in participants' stories. These themes introduce the roles of family connections, social capital, and third places in contributing to newcomers' sense of place. Leisure settings are highlighted, in particular, as sites of social learning, language skill development, and social connection.